2017
DOI: 10.17925/ohr.2017.13.02.117
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Oligometastases Secondary to Non-small Cell Lung Cancer—What is the Optimal Treatment Approach?

Abstract: B ackground: Five-year overall survival (OS) for patients with stage IV non-small cell lung cancer (NSCLC) is a dismal 1%. However, approximately 7% have limited or solitary metastases, including to the adrenal gland. Radical treatment of these oligometastases (OM) could increase local control and improve OS. Our objective was to critically analyze data describing aggressive treatment of adrenal OM secondary to NSCLC. Methods: A literature search examining English publications describing surgery or radiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…With the widespread use of regularly performed staging with CT or positron-emission-tomography (PET)-CT, and the growing recognition of the oligometastatic or oligoprogressive state in different tumor entities, the number of patients presenting with asymptomatic adrenal metastases has increased [32][33][34]. For these patients, surgical resection remains the gold standard, however, many patients are medically unfit for surgery, or their tumors are not technically resectable, and alternative local treatment approaches are required [4,16,35]. As the current literature on adrenal SBRT is still limited, a patterns-of-care analysis for patients treated with hypofractionated radiotherapy to their adrenal metastases was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread use of regularly performed staging with CT or positron-emission-tomography (PET)-CT, and the growing recognition of the oligometastatic or oligoprogressive state in different tumor entities, the number of patients presenting with asymptomatic adrenal metastases has increased [32][33][34]. For these patients, surgical resection remains the gold standard, however, many patients are medically unfit for surgery, or their tumors are not technically resectable, and alternative local treatment approaches are required [4,16,35]. As the current literature on adrenal SBRT is still limited, a patterns-of-care analysis for patients treated with hypofractionated radiotherapy to their adrenal metastases was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with good performance status can undergo surgery, and some studies have shown prolonged lifespan after adrenalectomy [4,6,24]. However, most patients do not have a level of performance that can support surgical treatment, and surgery cannot be performed for reasons such as location and tumor size [21,25,26]. In the review studies comparing radiosurgery to adrenalectomy, it should not be forgotten that SABR patients are generally patients with worse prognostic factors (2-year OS 44% vs 19%) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with good performance status can undergo surgery, and some studies have shown prolonged lifespan after adrenalectomy [4,6,24]. However, most patients do not have a level of performance that can support surgical treatment, and surgery cannot be performed for reasons such as location and tumor size [21,25,26]. In the review studies comparing radiosurgery to adrenalectomy, it should not be forgotten that SABR patients are generally patients with worse prognostic factors (2-year OS 44% vs 19%) [27].…”
Section: Discussionmentioning
confidence: 99%